PENGARUH KUALITAS LAYANAN, CITRA MEREK, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN KOPI KENANGAN DI JAKARTA - Yudi Iskandar, (2022)
The development of coffee drinkers in Indonesia has resulted in the emergence of brand coffee shop with a variety of unique themes, one of which is coffee memories as a pioneer of drinking coffee with the concept ready to drink. This study aims to determine, prove and analyze the influence of service quality, brand image, and customer satisfaction on customer loyalty due to the discovery of the phenomenon of customer loyalty at Kopi Kenangan in Jakarta. This study uses quantitative testing methods with primary data collection.. As for this study, non-probability sampling was used with the sampling technique used in the study, namely purposive sampling with a total sample taken of 100 customer respondents who had purchased the Kopi Kenangan product at the Kopi Kenangan outlet in Jakarta, and then an analysis of the questionnaire included validity and reliability analyzed descriptively and analysis using the SmartPLS 3.0 program. The primary data source was obtained from distributing questionnaires to customers who had purchased the Kopi Kenangan product in Jakarta. The results of testing this research show (1) Service quality has a significant and positive effect on customer loyalty for Kopi Kenangan in Jakarta. (2) Brand image does not have a significant effect on customer loyalty for Kopi Kenangan in Jakarta. (3) Customer satisfaction has a significant and positive effect on customer loyalty for Kopi Kenangan in Jakarta.